A Course-Based Qualitative Inquiry: What Relational-Centred Practice Looks Like When in a Power-Over Position of Authority - Cambridge, Adrianna; Fereja, Sarah; Mai, Irene; Yuan, Alice; Bellefeuille, Gerard (Advances in Social Sciences Research Journal, 2020)
In this article, we report on the innovative research design and results of a course-based qualitative inquiry into child and youth care (CYC) students’ experiences of maintaining a relational-centered practice stance while in a power-over position of authority. Qualitative data from two semi-structured focus groups as well as an arts-based data collection technique were analyzed using the thematic analysis method. The following four major themes were identified from the analyses: (a) “self-awareness is key,” (b) “the mediating power of a positive trusting relationship,” (c) “the vital importance of emotional safety,” and (d) “it’s a two-way street.” The results of this course-based study revealed that, although CYC students are committed to practicing relationally, the dynamics of being in a position of power-over authority are complex and challenging to navigate.